A sustainable energy option to the expanding Chennai metropolitan area - Palanichamy, Palanichamy (2015)
India is experiencing rapid growth in inhabitants, economic reforms and industrial development, which lead to a significant upsurge in waste generation. Though burgeoning amount of waste generated is an index for India's socioeconomic development and economic prosperity, its management is an indispensable task to achieve defensible growth, was not given priority during the last decades. Moreover, the on-going solid waste management systems are found to be insignificant, impetuous, topsy-turvy, expensive, human-intensive, unsafe to human and environment. Furthermore, attempts on electricity generation from waste resulted in the closure of their operation owing to improper planning on the quantity of waste generated and its composition, inadequate public cooperation, lack of technical know-how and financial crisis. As India is to ensure passable energy provisions at an affordable cost to its citizens with environmental concern, after careful study and lessons learnt from the failures of the former waste to energy projects, this paper proposes a successful environmental friendly waste to energy project for the expanding Chennai metropolitan area, India.